The Rise and Fall of the Mental Health Recovery Model - Brian , I Field (International Journal of Psychosocial Rehabilitation, 2016)
The recovery model in mental health was the result of a number of coinciding events that include economic issues, social movements and consumer rights. This led to a new approach to mental health treatment. However the economic issues led to a new political agenda arising. Neo liberalism saw the decline in mental health consumers gaining empowerment and an equal share for the responsibility of their own treatment. This paper looks at a number of reasons why this model was introduced, the history behind it being introduced and why it has been largely ineffective in becoming a dominant model within mental health practice